SEXIST BIAS MANIFESTED IN THE LANGUAGE OF NURSERY RHYMES: ANALYSIS OF SEXIST LINGUISTIC FEATURES - Ra'ed Awad Al-Ramahi (European Scientific Journal, ESJ, 2013)
Nursery Rhymes have been used for long time as a tool to make babies relax and sleep or even to help children at schools enjoy their time singing them. However, these rhymes are full of massive amount of language that is extremely sexist. The sexism of language comes because of the male's dominant voice and powerful image drawn through out the rhymes. In fact, there are some studies that are concerned with sexism in the language of fairy tales and other genres. However, studies on sexist linguistic features of nursery rhymes are rarely found. This article aims to present the different linguistic forms and patterns that help building up the sexist facets of the entire texts of the rhymes. For this purpose, a number of nursery rhymes featuring sexist has been selected and analyzed. The research has been conducted with the help of reviewing some principles of Critical Discourse Analysis and considering some feminist views. As a result, the ideologies that structure and underlie the linguistic expressions of the texts (nursery rhymes) have been uncovered.